A novel dual-key management protocol based on a hierarchical multicast infrastructure in mobile internet. (9th April 2009) - Cao, Jiannong; Liao, Lin; Wang, Guojun; Ma, Hao; , Bin Xiao
This paper describes a secure multicast infrastructure for large-scale group communication in mobile Internet and proposes a key management protocol based on it. The hierarchical infrastructure logically divides the key management domain into several smaller administratively scoped areas with a key server associated with each area respectively. All the key servers located in every area participate in a Public Key Infrastructure (PKI) as trusted entities known by the subgroup members. Therefore, it is efficient to minimise the re-keying overhead implemented in the mobile host tier and simplify the re-keying relationships between the distributed key servers.